ANALISIS PENGARUH KUALITAS PRODUK, LOKASI DAN GAYA HIDUP HEDONISME TERHADAP KEPUTUSAN PEMBELIAN PRODUK COFFESHOP HYPERMUT - Suryani, Jane Angrey; Lubis, Junita; Ritonga, Mulkan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to determine the effect of product quality, location, hedonism lifestyle on purchasing decisions for hypermut coffeshop products. This type of research is associative research. Data collection in this study was carried out through a survey approach with a descriptive quantitative research type by distributing questionnaires to 100 respondents, while the population used in this study were hypermut coffeshop customers. Data collection techniques were carried out by interview, questionnaire and documentation study. The data analysis tool used in this study uses SEM-PLS. The data analysis technique in this study is descriptive analysis, hypothesis testing using partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results showed that product quality, location, hedonism lifestyle had a positive and significant effect on customer loyalty both simultaneously and partially.